Warisan Gelap Kekerasan: Menguak Budaya Perundungan di Sekolah Dasar dalam Novel Haniyah dan Ala di Rumah Teteruga Karya Erni Aladjai - Sajidah Nur; Taufik Dermawan; Karkono Karkono (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The purpose of this study is to examine the portrait of bullying in the novel Haniyah and Ala at Teteruga's House. This study uses a qualitative approach. The research data are in the form of dialogues and narratives that describe bullying. The data source for this research is the novel Haniyah and Ala at Teteruga's House by Erni Aladjai. Data collection was carried out using documentation techniques. Data validity was tested using credibility techniques, while data analysis was carried out using a flow model. The results of the study indicate that the character Ala experienced bullying from a teacher (Mrs. Hijima) and her peers for five years. The teacher who bullied Ala was a victim of bullying from her teacher during elementary school, and she repeated this form of violence to her students. In addition, Ala's peers began bullying after seeing Mrs. Hijima's actions against her. These findings indicate that violence has become a normalized and inherited culture in the educational environment. The bullying experienced by Ala caused traumatic impacts, namely reluctance to go to school and trauma accompanied by physical symptoms. However, Ala was able to face and stop the bullying. Based on the research results, there are three important implications. First, anti-bullying education needs to be implemented at the elementary, secondary, and tertiary levels for both educators and students. Second, any violence in schools disguised as discipline and learning deserves to be reexamined. Third, programs to break the chain of bullying need to be implemented in various educational institutions. Abstrak Tujuan penelitian ini adalah mengkaji potret perundungan dalam novel Haniyah dan Ala di Rumah Teteruga. Penelitian ini menggunakan pendekatan kualitatif. Data penelitian berupa dialog dan narasi yang menggambarkan perundungan. Sumber data penelitian ini adalah Novel Haniyah dan Ala di Rumah Teteruga karya Erni Aladjai. Pengumpulan data dilakukan dengan teknik dokumentasi. Keabsahan data diuji menggunakan teknik kredibilitas, sedangkan analisis data dilakukan dengan model alir. Hasil penelitian menunjukkan bahwa tokoh Ala mengalami perundungan dari seorang guru (Ibu Guru Hijima) dan teman-teman sebayanya selama lima tahun. Guru yang merundung Ala merupakan korban perundungan dari gurunya semasa sekolah dasar, dan ia mengulangi bentuk kekerasan tersebut kepada siswanya. Selain itu, teman-teman sebaya Ala mulai merundung setelah melihat tindakan Ibu Guru Hijima terhadapnya. Temuan ini menunjukkan bahwa kekerasan menjadi budaya yang dinormalisasi dan diwariskan di lingkungan pendidikan. Perundungan yang dialami Ala menimbulkan dampak traumatis, yakni keengganan untuk sekolah dan trauma yang disertai gejala fisik. Kendati demikian, Ala mampu menghadapi dan menghentikan perundungan tersebut. Berdasarkan hasil penelitian, terdapat tiga implikasi penting. Pertama, pendidikan antiperundungan perlu diselenggarakan di tingkat dasar, menengah, dan tinggi bagi pendidik maupun peserta didik. Kedua, setiap kekerasan di sekolah yang berkedok pendisiplinan dan pembelajaran patut dipertanyakan ulang. Ketiga, program pemutusan rantai perundungan perlu diadakan di berbagai institusi pendidikan.